2016
DOI: 10.5114/fmpcr.2016.63694
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent pneumatic compression in patients with postmastectomy lymphedema

Abstract: Background. Postmastectomy lymphedema frequently affecting young patients constitutes a personal, family and social problem. For this reason, primary care physicians often consult both patients and their families. Objectives. the aim of this study was to evaluate the effects of intermittent pneumatic compression (iPC) alone or in combination with exercises on upper limbs circumference and hand function. Material and methods. the study population consisted of 21 patients with breast cancer-related lymphedema. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The front-end upsampling is to enlarge the low-depth learning digital features to the specified image size through bicubic interpolation and other methods after the low-depth learning digital features are input to the network [22]. Meta Analysis Convolutional Neural Network (SRCNN) is the first to apply deep learning to Meta analysis image reconstruction, using a three-layer convolutional neural network to fit the mapping between amplified low-depth learning digital features and high-depth learning digital features Relationship, and achieved a good reconstruction effect [23].…”
Section: Meta Analysis Reconstruction Theorymentioning
confidence: 99%
“…The front-end upsampling is to enlarge the low-depth learning digital features to the specified image size through bicubic interpolation and other methods after the low-depth learning digital features are input to the network [22]. Meta Analysis Convolutional Neural Network (SRCNN) is the first to apply deep learning to Meta analysis image reconstruction, using a three-layer convolutional neural network to fit the mapping between amplified low-depth learning digital features and high-depth learning digital features Relationship, and achieved a good reconstruction effect [23].…”
Section: Meta Analysis Reconstruction Theorymentioning
confidence: 99%
“…Previous study have analyzed manual lymphatic drainage for lymphedema following breast cancer treatment and they found that it is safe and may offer extra benefit to compression bandaging for swelling diminishment [7], another examination have examined administration of low level laser treatment (LLLT) in women with breast cancer related lymphedema and they concluded that LLLT with bandaging may offer an efficient helpful choice to conventional manual lymphatic drainage [8]. Additionally another study has assessed the impacts of intermittent pneumatic compression (IPC) alone or in combination with exercises, it was concluded that IPC is a powerful method of decreasing upper limb edema in postmastectomy women [9]. Concerning treatment of CTS, a study was designed to compare the efficacy of ultrasound and laser treatment for CTS and it was concluded that ultrasound treatment was more effective than laser for treatment of this disorder [10], another investigation have explored the efficiency of extracorporeal shock wave therapy (ESWT) for treating patients with CTS and the outcomes demonstrated that ESWT is a significant and novel procedure for patients with CTS [11].…”
mentioning
confidence: 99%